Blood pressure changes following combined instrumental music therapy and ginger decoction foot hydrotherapy among patients with hypertension - Fernando Perdana; Riska Oktalina; Sujiah Sujiah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is a major global health problem that contributes to increased morbidity and mortality from cardiovascular disease. Blood pressure control can be supported by non-pharmacological approaches, including safe and easy-to-implement complementary therapies such as instrumental music therapy and ginger decoction hydrotherapy. Purpose: To analyse the effectiveness of combined instrumental music therapy and ginger decoction hydrotherapy on blood pressure in patients with hypertension. Method: A quantitative quasi-experimental study with a one-group pre-test and post-test design was conducted among patients with hypertension at Kedaton Community Health Center, Bandar Lampung. 15 patients were initially recruited using purposive sampling, and 15 respondents with complete intervention and pre-test and post-test data were included in the final analysis. The intervention combined slow-tempo instrumental music therapy and ginger decoction foot hydrotherapy for 15 minutes daily over five days. Blood pressure was measured before and after the intervention and analysed using the Wilcoxon signed-rank test at a significance level of p < 0.05. Results: The mean age of the respondents was 54.80 years, and most were female. Before the intervention, the mean systolic and diastolic blood pressures were 156.00 mmHg and 98.67 mmHg, respectively. Following the combination of instrumental music therapy and ginger decoction hydrotherapy, the mean systolic blood pressure decreased to 138.67 mmHg, while the mean diastolic blood pressure decreased to 86.67 mmHg. The Wilcoxon signed-rank test showed a significant difference in both systolic and diastolic blood pressure before and after the intervention (p < 0.001). Conclusion: The combination of instrumental music therapy and ginger decoction hydrotherapy was effective in reducing blood pressure among patients with hypertension. This combination may be considered a supportive non-pharmacological intervention in community nursing and primary healthcare settings. Further studies using a controlled experimental design and longer intervention duration are recommended to strengthen the evidence. Keywords: Blood Pressure; Ginger Decoction Hydrotherapy; Hypertension; Instrumental Music Therapy; Non-Pharmacological Therapy.